AN EFFECTIVE PROCESS OF ORGANIZATIONAL COMMUNICATION: AN INTERCULTURAL COMMUNICATION APPROACH - Muharto Toba (The Indonesian Journal of Communication Studies, 2015)
In general, an effective communication is something so difficult to do. The communication process always involves cross cultural factors which would form a potential communication problems. These factors are, such as semantic problems, is that the same of words but having different meaning by the communicators that come from different cultures. Also, the problems are related with tone and intonation voices, perception, etc that come from different clusters of social and cultures.In the organization, the differences that come from different clusters of cultural society are also potential to become barriers of the effective communication which results in incorrect interpretation, evaluation and perception. More over if the boss suffered by “a hard to hearing disease”, as results of differences of position and class that owned by the boss, the barriers would be grow bigger and bigger. The other problems could be come from the Indonesian ethnic groups who embrace “high-context culture”, so that the information such as advice, complain, critic, etc., do not need to be submitted in words, verbal forms. In the high-context culture’s groups, information obtained by conclusion, behavior, and even in silences. More over if the process is related to the superior-subordinate position, so that the process of communication becomes an ineffective one. The boss is often seeing that the messages come from the subordinates is negative, not qualified, so it does not to be heard. If it happens it could cause anxiety and reluctance of subordinates to deliver the right information. Adverse impact of the organization is the existence of subordinate’s dissatisfaction and distrust of the superiors, and therefore contributes the overall organizational performance.This description reveals the barriers that exist in a cross cultural communication in order to achieve an effective organizational communication. The approach used is descriptive qualitative, which produces description of the behavior of certain individuals in an organization and analyzed from the point of view of a thorough and complete. The data obtained from several sources who have worked in an organization for a long time. The author uses the theory of triangulation of sources, methodological, and theories to obtain reliable data. The description of the findings in this paper is the need for cross-cultural approach to organizational communication to achieve an effective communication.